Plantão Psicológico na UFMG : história de um serviço - Maria Clara Rabelo Ferreira Silva (2022)
This research intends to recover the memory and history of the Psychological Duty of the Psychology university clinic of the Psychology graduation course of the College of Philosophy and Human Sciences (FAFICH) of the Federal University of Minas Gerais (UFMG) since there are various gaps in this history and there is a danger of them not being filled. From the perspective of Social Psychology, memory is not merely something given by itself, but has to do with a shared whole that sustains and gives meaning to what and how things will be remembered. Thus, we seek to understand the horizon in which memory takes place and how it is constituted from it. In this sense, memory and history are akin to hermeneutics, which indicates how each epoch has its own worldview, so that everything that happens within that space of time and that place is an expression of that period. Sense analytics is the methodology used. It sustains that people collectively support the meanings for what reality is and what is presented in it. Such shared meanings are, necessarily, historical, insofar as what and how things are being composed and happening in everyday life and, somehow, solidifying into more habitual ways of using and dealing with reality. The loss of the historical and constitutive dimension of how things come to be what they are is the risk in this world movement. Thus, there is a risk of falling into a mere repetition of practices without a clear understanding of how historical they are and came to be, which means they can be constituted again, that is, transformed. In this logic, the Psychological Duty in question was a practice sedimented over time and through its recurrent occurrence. Thus, it is necessary to revisit its sedimentation in order to unveil the historical process present in its constitution, and to release it to new configurations and conformations without the threat of losing it into oblivion. In order to do this, six interviews were carried out with authors and actors of this history. They were transcribed, read and analyzed in order to compose a polyphonic narrative woven by the researcher - and current on- duty psychologist. As a result of this work, a history of the UFMG Psychological Service was composed, starting with its origin in the Psychological Counseling Service of the University of São Paulo (USP), going through the 25 years of service at UFMG. Subsequently, it was found that, in addition to structural differences over the years, the service remains the same. All on-duty psychologists and psychologists in training belong to the same destiny community, that is, they share common values and beliefs that have guided and continue to guide the service, such as listening, being present and being available to meet those who seek help.